Design and Methodology of a Multicenter Randomized Clinical Trial to Evaluate the Efficacy of Tongmai Jiangtang Capsules in Type 2 Diabetic Coronary Heart Disease Patients - Wang, Yu; Guo, Yilei; Lei, Ye; Huang, Shuwei; Dou, Liping; Li, Chang; Zhao, Buchang; Fu, Wei; Zhou, Peng; Wan, Haitong; Zhao, Mingjun; Yang, Jiehong (Frontiers in Pharmacology, 2021)
Background: Population-based studies have consistently showed an increased incidence of coronary heart disease (CHD) and cardiac mortality in patients with type 2 diabetes mellitus (T2DM). Tongmai Jiangtang capsules (TJC) are Chinese patent medicines that have been approved in China for the treatment of diabetic vascular complications. However, the evidence supporting the efficacy and safety of TJC in T2DM associated with CHD remains unclear. Here, we designed a randomized, parallel-controlled clinical trial to investigate a new complementary therapy for T2DM patients with CHD. Methods: A total of 360 T2DM subjects associated with CHD (aged 18-75 years) will be randomly assigned to the TJC group or placebo group at a 2:1 ratio. On the basis of western medicine therapy, all the participants will receive TJC or placebo, orally, 3 capsules/time, thrice daily for 12 weeks. The primary outcomes are the Canadian Cardiovascular Society (CCS) classification. All statistical analyses will be performed at a two-sided 0.05 significance level, using SAS 9.4 statistical software. Discussion: This trial will evaluate the efficacy of TJC for the treatment of CHD in T2DM patients. The results of the study will provide reliable clinical research evidence for application of TJC in treating CHD in T2DM patients. Clinical Trial registration: The trial is registered in the Chinese Clinical Trial Registry (No. ChiCTR2000037491), http://www.chictr.org.cn/enIndex.aspx.